Characterization of the induction of nitric oxide synthase and cyclo-oxygenase in rat aorta in organ culture - Bishop-Bailey, David (1997)
1. Within vessels, the formation of nitric oxide (NO) or prostaglandins is normally catalysed in the endothelium by constitutive isoforms of NO synthase (eNOS) and cyclo-oxygenase (COX-1), respectively. However, during inflammatory conditions, the underlying smooth muscle acquires the ability to release NO and prostaglandins after the expression of inducible isoforms of NOS (iNOS) and COX (COX-2). The co-induction of iNOS and COX-2 has been studied over 24 h in isolated vascular smooth muscle cells in vitro. However, due to the limitation of using cultured cells, the relationship between the activities of iNOS and COX over longer periods has not been addressed. Moreover, the relative contribution of the endothelium to the production of NO and prostaglandins under inflammatory conditions is not completely understood. 2. Here using an organ culture system, we have determined the profile of COX (6-keto prostaglandin F(1α) (6-keto PGF(1α)), PGE(2), thromboxane B(2) (TXB(2)) and NOS (nitrite and nitrate) metabolites released over a period of 10 days from segments of rat aorta. In each case, segments from the same animal were left untreated or treated with bacterial lipopolysaccharide (LPS; 10 μg ml(−1)) in order to induce iNOS and COX-2. Prostaglandins were measured by radioimmunoassay whilst nitrite and nitrate were measured, respectively, by Greiss reaction alone, or following a nitrate reductase step. The isoforms of NOS and COX responsible for metabolite release were characterized pharmacologically by use of inhibitors and at the molecular level by reverse transcription polymerase chain reaction with specific primers for iNOS, eNOS, COX-1 and COX-2. In separate experiments the role of the endothelium in the release of nitrite, nitrate and prostaglandins and in the expression of iNOS, eNOS, COX-1 and COX-2 was determined by comparing responses in endothelium denuded and endothelium-intact segments of rat aorta. 3. Under control culture conditions vessels released prostaglandins in the following rank order 6-keto PGF(1α)=PGE(2)>>TXB(2). LPS increased the release of 6-keto PGF(1α) and PGE(2) but not of TXB(2), an effect that was inhibited by the protein synthesis inhibitor cycloheximide (1 μM), the anti-inflammatory steroid dexamethason (1 μM), the nonsteroidal anti-inflammatory drug indomethacin (30 μM) and, where tested, the selective COX-2 inhibitor NS-398 (30 μM). Similarly, segments of rat aorta released detectable levels of nitrite and nitrate, which were reduced by N(G)-nitro-L-arginine methyl ester (L-NAME, 1 mM), which inhibits all isoforms of NOS, and by dexamethasone (1 μM), which inhibits the induction of iNOS. The proportion of nitrate to nitrite released over the 10 day period varied greatly from approximately 1 : 1 on days 5 to 8 to 5 : 1 on day 9. However, the sum of nitrite and nitrate (NOx) as well as PGE(2) remained elevated over the whole 10 day period. The formation of 6-keto PGF(1α) peaked on days 1 and 2. 4. In freshly prepared tissue, mRNAs for eNOS, COX-1, iNOS and COX-2 were detected. After 24 h in culture, there was an apparent increase in the level of mRNAs for iNOS and COX-2 but not for eNOS or COX-1, an effect that was further enhanced when LPS was included in the culture medium. The expressions of mRNA for eNOS, COX-1, iNOS or COX-2 were not greatly different in vessels with intact or disrupted endothelium. Similarly the release of NOx or PGE(2) by vessels after the 1st or 9th day in culture were not significantly different from vessels prepared with or without endothelium. 5. Thus, COX-2 and iNOS are co-induced in intact vessels in culture, with the vascular smooth muscle being the main site of mediator generation. In contrast to data from isolated cells in culture (observed usually over 1 day), both COX and NOS activities in cultured blood vessels were elevated for at least 10 days. Also, unlike isolated cells in culture, the COX and NOS pathways were active independently; L-NAME had little effect on the activity of COX and indomethacin had little effect on the activity of NOS.